Poverty, gender, and reproductive choice : an analysis of linkages - Mukhopadhyay, Swapna; Savithri, R. (New Delhi : Manohar, 1998)
Study conducted in Uttar Pradesh and Karnataka, India.
Includes bibliographical references (p. [120]-124) and index.
Keywords: Poverty -- India; Poor women -- India; India -- Economic conditions -- 1947-; India -- Social conditions -- 1947-